Serum nitric oxide and homocysteine as biomarkers of ectopic pregnancy - Meiyappan, Kavitha; Dhiman, Pooja; Rajendiren, Soundravally; Thayagarajan, Krishnalatha; Raghavan S, Soundara (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Aim of current study was to evaluate the role of serum homocysteine and nitric oxide in the diagnosis of ectopic pregnancy. Methods: The study included 32 patients with ruptured ectopic, 29 miscarriage patients and 30 normal pregnant women as controls. Fasting plasma homocysteine, serum folate, vitamin B12 levels and nitric oxide levels were estimated at the time of admission. Results: Plasma homocysteine levels were significantly lower in patients with ectopic pregnancy than normal pregnancy. Nitric oxide levels were significantly lower in patients with abortion. Conclusions: Patients with abortion have decreased circulating nitric oxide levels in serum while those with ectopic pregnancies have decreased homocysteine levels.